Stool antigen immunodetection for diagnosis of Giardia duodenalis infection in human subjects with HIV and cancer - Nooshadokht, Maryam; Kalantari-Khandani, Behjat; Sharifi, Iraj; Kamyabi, Hossein; Liyanage, Namal P.M.; Lagenaur, Laurel A.; Kagnoff, Martin F.; Singer, Steven M.; Babaei, Zahra; Solaymani-Mohammadi, Shahram (Journal of microbiological methods, 2017)
Human infection with the protozoan parasite Giardia duodenalis is one the most common parasitic diseases worldwide. Higher incidence rates of giardiasis have been reported from human subjects with multiple debilitating chronic conditions, including hypogammaglobulinemia and common variable immunodeficiency (CVID). In the current study, stool specimens were collected from 199 individuals diagnosed with HIV or cancer and immunocompetent subjects. The sensitivity of microscopy-based detection on fresh stool preparations, trichrome staining and stool antigen immunodetection for the diagnosis of G. duodenalis were 36%, 45.5% and 100%, respectively when compared with a highly sensitive stool-based PCR method as the gold standard. Further multilocus molecular analyses using glutamate dehydrogenase (gdh) and triose phosphate isomerase (tpi) loci demonstrated that the AI genotype of G. duodenalis was the most prevalent, followed by the AII genotype and mixed (AI+B) infections. We concluded that stool antigen immunodetection-based immunoassays and stool-based PCR amplification had comparable sensitivity and specificity for the diagnosis of G. duodenalis infections in these populations. Stool antigen detection-based diagnostic modalities are rapid and accurate and may offer alternatives to conventional microscopy and PCR-based diagnostic methods for the diagnosis of G. duodenalis in human subjects living with HIV or cancer. •Stool antigen-based modalities are as sensitive as PCR-based techniques for the diagnosis of G. duodenalis infection•AI genotype of Giardia duodenalis was the most common parasite found in patients with HIV and cancer•Molecular identification of G. duodenalis using the gdh and tpi loci were consistent in patients with HIV and cancer